Environmental barriers to participation in children with cerebral palsy aged 5 to 12 years - Gulanikar, Apurva A.; Ekbote, Amruta G.; Nathani , Franny M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Cerebral palsy is a group of permanent disorders of development in movement and posture causing various limitations. India has a prevalence of 2.95 CP children per 1000 children. Participation is important for overall development. Participation is influenced by factors around the child and family. Environmental factors include social support, accessibility, accommodation, and availability of facilities. There is dearth of literature about what environmental barriers prevent individuals with cerebral palsy from attaining participation in Indian surroundings. Thus, the aim was to find the environmental barriers faced to participation. Methods: Parents of 30 children with CP from Pune participated in the study. Convenience sampling was used to onboard them. Ethical clearance, informed consent and assent were taken. They had to fill out the CHIEF questionnaire- Craig’s hospital inventory of environmental factors and the therapist determined the GMFCS and MACS level of the child. Results: Barriers to participation as reported by parents were 48.07% in the policies subscale, 23.47% in the physical/structural subscale, 4.55% in the school subscale, 34.29% in the attitude/support subscale and 37.86% in the services/assistance subscale. Conclusions: The results showed barriers to participation were most common in the policies subscale and the services and assistance subscale. Policymakers and administrative heads in sectors across government, transport, and educational institutes need to take the requirements of children with cerebral palsy into consideration.